2000
DOI: 10.1002/1529-0131(200007)43:7<1647::aid-anr31>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of muscarinic receptor autoantibodies on parasympathetic neurotransmission in Sjögren's syndrome

Abstract: Objective. Sjögren's syndrome (SS) is an autoimmune disorder characterized by dry eyes and mouth (sicca syndrome) and lymphocytic infiltration of the lacrimal and salivary glands. Abnormalities of parasympathetic neurotransmission may contribute to the glandular dysfunction. In this study, we used a functional assay to investigate autoantibody-mediated effects on parasympathetic neurotransmission and smooth muscle contraction.Methods. Serum and purified IgG were obtained from patients with primary and secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
6

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 220 publications
(88 citation statements)
references
References 26 publications
4
78
0
6
Order By: Relevance
“…The reversibility of the binding observed when mouse or human submandibular acinar cells are exposed to SS IgG or rabbit polyclonal anti-M 3 R is intriguing since it confirms the previous findings in Ig -null mice (71) but is contradictory with data obtained from smooth muscle bioassay (15,62,64) and radioligand binding studies (14,73). In myasthenia gravis it is established that, in vitro, the reversibility of the interaction between the autoantibodies and the nicotinic cholinergic receptors is highly dependent on the length of time of exposure and the concentration of the autoantibody (85).…”
Section: Induction Of Cholinergic Hyperresponsiveness By Passive Transupporting
confidence: 47%
See 1 more Smart Citation
“…The reversibility of the binding observed when mouse or human submandibular acinar cells are exposed to SS IgG or rabbit polyclonal anti-M 3 R is intriguing since it confirms the previous findings in Ig -null mice (71) but is contradictory with data obtained from smooth muscle bioassay (15,62,64) and radioligand binding studies (14,73). In myasthenia gravis it is established that, in vitro, the reversibility of the interaction between the autoantibodies and the nicotinic cholinergic receptors is highly dependent on the length of time of exposure and the concentration of the autoantibody (85).…”
Section: Induction Of Cholinergic Hyperresponsiveness By Passive Transupporting
confidence: 47%
“…Although SS is classified as an autoimmune disease, no specific pathologic autoantibody has been found (3,13). However, data from recent studies have suggested that patients with primary SS and patients with secondary SS may have inhibitory autoantibodies directed against muscarinic receptors (14)(15)(16). The presence of inhibitory autoantibodies directed against salivary gland muscarinic receptors would serve to unite the pathologies underlying the glandular hypofunction of both primary and secondary SS, explaining why the degree of glandular hypofunction is equivalent in the two (17).…”
Section: Introductionmentioning
confidence: 99%
“…23 Likewise, persistent loss of sensitivity to Ach was reported in salivary acinar cells that obtained from SS patients. 24 Interestingly, SS IgG induced a similar degree of inhibition in the CChevoked bladder contraction by approximately 50%, 25 suggesting that CICT is also reduced in this tissue, because [Ca 2 þ ] i also plays a putative role in smooth muscle contractions.…”
Section: Discussionmentioning
confidence: 92%
“…In human salivary glands, binding of anti-M3R autoantibodies (Nguyen et al 2000;Waterman et al, 2000) would initially be expected to cross-link receptors and trigger internalization and a decrease in receptor number. However to compensate for this short-term change, an increase in receptor density appears to occur (present study).…”
Section: Mechanisms Resulting In Receptor Up-regulationmentioning
confidence: 99%
“…Dawson et al (2001) demonstrated changes consistent with receptor down-regulation: a decrease in muscarinic receptor sensitivity in salivary acinar cells with no change in the maximal response to muscarinic receptor stimulation. Functional anti-muscarinic receptor antibodies have been demonstrated in the serum of patients with primary Sjögren's syndrome (pSS) and these inhibit parasympathetic neurotransmission (Waterman et al, 2000). Such an inhibition of neurotransmission might be predicted to cause a compensatory up-regulation of M3R number.…”
mentioning
confidence: 99%